2016
DOI: 10.1149/2.1131609jes
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Li Ion Electrolytes Composed of Li3AsS4Alloyed with Li4GeS4

Abstract: First principles computational techniques are used to study properties of promising Li ion electrolytes, recently developed at Oak Ridge National Laboratory, based on alloys having the composition Li3 + xAs1 − xGexS4. The crystal structure of pure Li3AsS4 is found to be characterized by the Pmn21 space group. Based on modifications of this structure, reasonable models of the x = 1/4 and x = 1/3 alloys are found to be in good agreement with the experimental X-ray diffraction patterns and to be consistent with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The partial density of states of Li 4 GeS 0 4 in its ground state structure was previously presented in Ref. 27. While, density functional theory is known to systematically underestimate the band gaps, the relative band gaps are usually well represented.…”
Section: Electronic Structure Resultsmentioning
confidence: 99%
“…The partial density of states of Li 4 GeS 0 4 in its ground state structure was previously presented in Ref. 27. While, density functional theory is known to systematically underestimate the band gaps, the relative band gaps are usually well represented.…”
Section: Electronic Structure Resultsmentioning
confidence: 99%
“…AIMD simulation studies of other Li sulfide SEs, such as Li 7 P 3 S 11 and argyrodite Li 6 PS 5 Cl, confirmed their exceptionally fast Li‐ion diffusion in bulk phases. In addition to these AIMD simulation studies, which quantified the overall diffusional properties, static first principles studies including NEB calculations have also been performed on Li sulfide SEs, such as Li 3 PS 4 , Li 4 GeS 4 , Li 4 SnS 4 , and Li 3 AsS 4 , to investigate the formation energies of mobile Li + vacancies and interstitials, Li + site energies in the structures, and Li + migration energy barriers …”
Section: Li‐ion Transport In Li‐ion Sesmentioning
confidence: 99%
“…Experimentally determined and theoretically calculated activation energy barriers E a of tetrahedral lithium ion migration in lithium sulfides possessing the hcp -type sulfur anion sublattices with respect to the electronegativity of nonlithium cation element M and sulfur anion Bader charges. Lithium sulfides in each subplot are structurally similar to the same space group. The corresponding data of E a , anion charge, and electronegativity of M are also listed in Table S2.…”
Section: Resultsmentioning
confidence: 99%